HUBUNGAN ANTARA IKLIM ORGANISASI DAN KEPUASAN KERJA DENGAN KOMITMEN TERHADAP ORGANISASI (Studi Kasus Pada Pegawai Salak Tower Hotel, Bogor) - Rudini Rudini; Widodo Sunaryo; Anoesyirwan Moeins (MAGMA : JURNAL MAGISTER MANAJEMEN, 2021)
The purpose of this study was to analyze the relationship between organizational climate and job satisfaction together with commitment to employee organization. The population in this study were staff at Salak Tower Hotel, Bogor which amounted to 145 people, determining the number of samples using slovin formula as many as 107 people. The approach of this research is correlational consisting of two independent variabels, namely Climate Organization and Job Satisfaction, while the dependent variabel is Commitment to Organization. Analytical techniques use multiple correlation, partial correlation and dimensional analysis.The results show that (1) There is a positive and significant relationship between Climate Organization (X1) with Commitment to Organization (Y), ryx1 = 0,994). (2) There is a positive and significant relationship between Job Satisfaction (X2) and Commitment to Organization (Y), (ryx2 = 0,992). (3) There is a relationship between Organizational Climate (X1) and Job Satisfaction (X2) together with Commitment to Organization (Y), (ryx1.2 = 0.995). Thus it can be concluded that Commitment to the Organization can be improved through Organizational Climate and Job Satisfaction.